Purificação e caracterização de uma nova substância com atividade anestésica local do veneno das glândulas parotóides do Bufo paracnemis - Patrocínio, Manoel Cláudio Azevedo (1997)
Amphibian skin has a diversity of substances, such as biogenic amines, alcaloids, steroids, proteins and peptides that evoke many pharmacological effects. In this study it was purified and characterized a factor with a local anesthetic activity. The venom extracted from Bufo paracnemis paratoid glands was dissolved in ethanol (1:5; w:v) and it was kept at 4 °C ovemight. Then the mixture was centrifugated at 5000 g for 5 minutes and the pellets were discarded. The supematant was fractionated by High Performance Liquid Chromatography (HPLC) using a C 18 column (2,5x30 cm) eluted with a flow of 7 ml/min with a gradient of 0-40% acetonitrile. The fractions were lyophilized for bioassay. A peak that presented motor paralysis after i.p. injection in mice was collected for further pharmacological studies. The fraction blocked comeal reflex in rabbit. This peak caused concentration dependent reduction in the rat phrenic nerve-diaphragm preparation. This inhibition was complete in high concentrations of the factor. The peak abolished the electrically evoked contraction on the longitudinal muscle of the mouse vas deferens. It decreased licking in the first phase and it abolished licking in the second phase of the formalin test in mice. The purity of this factor was also demonstrated by thin layer chromatography. There were performed infrared spectroscopy and mass spectrometry. The molecular weight was determined and it was 402 Da. Its structure belongs the family of the group of the steroids. It’s a bufogenin. It was made a structural proposition and nothing is known of the activity of this purified factor. In conclusion, the results presented in this study showed the total purification of a potent local anesthetic factor from Bufo paracnemis skin secretions that may be used in future human therapeutics.